ANALISIS KUALITAS TERJEMAHAN ARTIKEL MEDIA OLEH MAHASISWA PRODI D-3 BAHASA INGGRIS POLITEKNIK - Alief Sutantohadi (Jurnal Bahasa Inggris Terapan, 2017)
This qualitative–inductive research is conducted to identify and describe the translation technics used by the students of D-3 programe of English Department of State Polytechnics of Madiun in translating the articles from The Jakarta Post daily newspaper. This research will also analise the the quality of  translation  result  and  its  relationship  with  the students’  competence  in  translation.  The  data  in  this research will be analised by using Content Analisis from Spradley. By using this technic, the data will be analised through some steps as domain analysis, taxonomic analysis, componential analysis and taking the cultural findings.  The result of the quality assesment of translation shows that the students’ competence in translation is adequate. This achievement is based on the result of assesment on the accuracy and the acceptability of the translation. The assesment on the accuracy of the translation shows from total 105 data were translated accurately for 66 data (62.86%) and then 21 data (20%) were translated less accurately     and  the  rest  for  18  data  (17.14  %)  were translated inacurately. The assesment result on acceptability of the translation shows from total 105 data were translated acceptable for 73 data (69.52%) and then 20 data (19.05%) were translated less acceptable and the rest for 12 data (11.43%) were translated unacceptable.Key Words    : the quality of translation, translation technique.